The Effect of Product Differentiation and Electronic Word of Mouth (E-Wom) on Consumer Purchasing Decisions of the Richeese Factory in Surabaya City - Arya Yudha Nugraha; Nuruni Ika Kusuma Wardani (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aimed to determine the effect of product differentiation and electronic word of mouth on consumer purchasing decisions of the Richeese Factory in Surabaya. This research used a quantitative research method and used the population of Richeese Factory consumers in Surabaya during the past year. A sample of 105 individuals was selected using non-probability sampling with an accidental sampling technique. Data was collected through conventional questionnaire distribution and measured using the Likert scale. The analysis utilized Partial Least Square (PLS). The results of this research indicated that each variable had a significant effect, both product differentiation and electronic word of mouth, on the consumer purchasing decisions of the Richeese Factory in Surabaya.